2008
DOI: 10.1075/aals.1.13nic
|View full text |Cite
|
Sign up to set email alerts
|

Roles learners believe they have in the development of their language learning – autonomy included?

Abstract: Through data generated in an ethnographic research project, which studies language learners (future English teachers), it was possible to observe that learners voice the importance of being in control of their own learning. Nevertheless, in the academic context, it seems they have an imaginary territory, where they can or cannot exercise autonomy. In the classroom, they agree that the one who owns the knowledge (teacher) should be in charge of class management, which includes the determination of content, dura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Reluctance by learners to take advantage of opportunities for autonomy within a classroom setting is also reported by Nicolaides (2008) in a study carried out at a Brazilian university. She noted, following learners' reports and her own classroom observations, that "where space is provided for them so that they can have an active role in their own learning, it is not taken up" (p. 152).…”
Section: Rejecting Autonomymentioning
confidence: 69%
“…Reluctance by learners to take advantage of opportunities for autonomy within a classroom setting is also reported by Nicolaides (2008) in a study carried out at a Brazilian university. She noted, following learners' reports and her own classroom observations, that "where space is provided for them so that they can have an active role in their own learning, it is not taken up" (p. 152).…”
Section: Rejecting Autonomymentioning
confidence: 69%
“…Students felt their freedom to follow their own beliefs and make their own decision was limited within the classroom. Using student teachers as participants, both Sert's (2006) and Nicolaides'(2008) studies imply that these student teachers will probably not adopt tools to promote autonomous learning amongst their future students as they themselves have been shaped by traditional ways of teaching.…”
Section: Significance Of Teachersmentioning
confidence: 99%
“…Several studies have shown the influence of teachers' learning experience on their current teaching behaviors (e.g. Borg, 2003, Nicolaides, 2008Sert, 2006). The teachers who had been shaped by traditional ways of learning are likely to behave in a similar way in their own classrooms.…”
Section: Scoresmentioning
confidence: 99%
See 2 more Smart Citations